PENGARUH OPINI AUDIT, UKURAN PERUSAHAAN, UKURAN KAP, DAN LEVERAGE TERHADAP ROTASI AUDITOR PADA PERUSAHAAN SEKTOR KEUANGAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE TAHUN 2018-2020 - Tuban Drijah Herawati; Wilis Aulia Wardah (TEMA, 2021)
This study aims to examine and obtain empirical evidence of the factors — influencing auditor rotation program in banking financial companies listed on the Indonesia Stock Exchange between 2018 and 2020 —including audit opinion, company size, Public Accounting Firm size, and leverage. The results indicated that audit opinion had no effect on auditor rotation program as both previous and current auditors have the same audit reference, Financial Accounting Standards, resulting in relatively similar opinions. Likewise, company size had no effect on auditor rotation program, meaning that auditor rotation program merely increase agency cost when the auditing quality by the Public Accounting Firm is good. The Public Accounting Firm size had a negative effect, implying that when the company used the Big Four Public Accounting Firm audit service, the company tended to maintain the previous auditor. Lastly, leverage has no effect on auditor rotation because companies with a high level of leverage will focus on improving financial performance instead of prevailing auditor rotation program.